1987
DOI: 10.1093/jac/20.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infections by staphylococci and other Gram-positive bacteria with teicoplanin: an open study

Abstract: Teicoplanin, 200-400 mg (3-6 mg/kg) daily iv or im, was used to treat 71 episodes of infection. The average duration of treatment was 22 days. The 64 evaluable episodes comprised 24 skin/soft tissue, 20 osteoarticular, ten urinary tract and one ventriculo-atrial shunt infections; one case of primary bacteraemia, three of endocarditis, two of pneumonia and three of pleural empyema. Fifty-five episodes were treated with teicoplanin monotherapy and nine with teicoplanin in association to other antibiotics. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…The concentration of teicoplanin in serum is proportional to the dose used, especially in healthy volunteers (24) and in patients with nonsevere underlying diseases (1,13). In our study, considerable variability in concentrations in serum was observed for both teicoplanin and vancomycin, although no relation was observed between peak or trough concentrations (at steady state) and outcome of infection.…”
Section: Discussioncontrasting
confidence: 45%
“…The concentration of teicoplanin in serum is proportional to the dose used, especially in healthy volunteers (24) and in patients with nonsevere underlying diseases (1,13). In our study, considerable variability in concentrations in serum was observed for both teicoplanin and vancomycin, although no relation was observed between peak or trough concentrations (at steady state) and outcome of infection.…”
Section: Discussioncontrasting
confidence: 45%
“…This study confirms that teicoplanin in combination with another antibiotic, usually an aminoglycoside, is effective for (9,12). This cure rate was not different from the reported 15 to 25% mortality rate for bacterial endocarditis (21).…”
Section: Discussionsupporting
confidence: 81%
“…All (1). In the present study, on the basis of SBA level monitoring, teicoplanin was administered at daily dosages at least twice as high as those previously used (1,8,11,14,25). In the present series, five patients with staphylococcal endocarditis were treated with teicoplanin alone, three had right-side endocarditis, and two were treated with teicoplanin plus surgery.…”
Section: Methodsmentioning
confidence: 90%
“…However, it has a longer elimination half-life, which allows once-a-day administration, and appears to be well tolerated (8,14,23). Although studies with animal models suggested good results with teicoplanin, alone or in combination with other antibiotics, for the treatment of infective endocarditis and other life-threatening infections (3,5,20), the results of recent clinical trials are somewhat conflicting (1,8,11,14,25). Moreover, only a few gram-positive-bacterial endocarditis cases were included in the above studies.…”
mentioning
confidence: 99%